Echeveria flammigera (Crassulaceae), a new name and status for E. pringlei var. parva - Rosales-Martínez, C. Santiago; Hernández-Campos, J. Daniel (Phytotaxa, 2023)
A revision of Echeveria pringlei var. parva was made based on morphological and biogeographical comparisons. The results show that this taxon should be raised to the species level and that it belongs to E. ser. Nudae. Since the epithet parva is unavailable for use due to the existence of E. parva, E. flammigera is proposed as a new replacement name. An updated description of the taxon is provided, as well as a distribution map.